IMPACT OF THE STRONG BOREAL SUMMER INTRASEASONAL OSCILLATION ON THE DIURNAL CYCLE OF RAINFALL OVER INDONE - Fatony Iswahyudi, Ridha
The diurnal cycle of rainfall in Indonesia is influenced by various modes of variability that alter the activity of the diurnal cycle of rainfall. The Boreal Summer Intraseasonal Oscillation (BSISO) is a mode of climate variability resulting from atmosphere-sea interactions with a direction of movement from the Indian Ocean to the western North Pacific Ocean. Previous research found an increase in afternoon rainfall over land and coastal areas when there is an increase in convective activity due to BSISO. Research on the impact of BSISO in Indonesia has found that convective activity during BSISO is associated with daily rainfall variability. However, research has yet to discuss the relationship between variations in convective activity, daily rainfall variability, and the diurnal cycle of rainfall in Indonesia. This study aims to determine the impact of strong-phase BSISO on Indonesia's diurnal cycle of rainfall. The impact of strong Boreal Summer Intraseasonal Oscillation (BSISO) on diurnal rainfall patterns in Indonesia was identified using Global Precipitation Measurement (GPM) during May - September (MJJAS) in 2011 - 2022. The strong BSISO category was determined using the BSISO index. A Butterworth bandpass filter was applied to dampen the effect of phenomena other than the BSISO period. Following the results of previous studies, BSISOs were composited based on the similarity of convective activity in Indonesia. The results show that the spatial pattern of convective activity is identical to the daily rainfall during BSISO. However, there are differences in the spatial pattern of daily rainfall with the diurnal component. The diurnal component of morning rain has positive rainfall anomalies over land and negative over the ocean. In contrast, afternoon rain has negative rainfall anomalies over land and positive rainfall anomalies over the ocean. Sumatra Island and Kalimantan Island have spatially significant diurnal patterns of rainfall in Indonesia. There is no difference in the amplitude of diurnal rainfall anomalies but there is a difference in the phase of the amplitude when BSISO occurs.